Novel solid-phase microextraction adsorbent for the forensic detection of accelerants in arson samples - Selvaraju, Geetha (2007)
Numerous adsorbents are available commercially as coatings for solid-phase microextraction (SPME) technique. However, some analytical methodologies might demand specific properties for the extraction of selected compounds. In this study, a simple, fast, effective and environmental friendly methodology for the determination of accelerants in arson samples using headspace-SPME coupled to gas-chromatographyflame ionization detector (GC-FID) is presented. A lab-made coated fiber prepared by sol-gel method, containing 1:1 molar ratio of octyltriethoxysilane (C8-TEOS): methyltrimethoxysilane (MTMOS) was employed in this technique. The fiber was tested for the headspace extraction of n-alkane standard hydrocarbons and common accelerants. Applicability of the fiber was demonstrated through the detection of accelerants in simulated arson samples. The C8-coated fiber showed a good selectivity for accelerants. Compared with commercial PDMS/DVB fiber, the lab-made coated fiber exhibited higher extraction capability for accelerants, higher thermal stability (up to 300 °C) and longer lifetime (~ 200 times usage). Electron microscopy experiment revealed that the surface of the fiber coating was well-distributed. A porous structure was suggested for the sol-gel derived C8 coating with an approximate thickness of (3-4) µm. The underlying mechanisms of the coating process were discussed and confirmed by infra-red (IR) spectrum. HS-SPME parameters, such as extraction time, extraction temperature and desorption time were optimized. The developed headspace-SPME method using C8-coated fiber showed satisfactory reproducibility (RSD < 6%), linearity (r > 0.9869) and detection limits for accelerants (0.7-1.0) µL. The lab-made SPME adsorbent was shown to be a good alternative to commercial SPME fiber for the determination of accelerants in arson cases.